Exploring consumer reactions to the recession in Slovenia and Bosnia and Herzegovina - Kolar, Tomaž (Managing global transitions, 2012)
In order to analyze the impact of the current economic crisis on consumers of FMCG products in the Balkan region this paper investigates changes and trends in consumer values and attitudes between years 2007 and 2009 in Slovenia and Bosnia and Herzegovina. A comparison of value ranks and factor scores between the two years and two countries shows some significant differences and surprising findings in terms of changes in consumer values and attitudes, which were otherwise expected to be relatively stable over a short time period. In order to provide an insight into questions of if, why and how the crisis differently affected Slovene and Bosnian consumers, possible causes for identified differences are discussed from the theoretical and practical standpoint and several managerial implications are suggested.
Keywords: attitudes; Bosna in Hercegovina; Bosnia and Herzegovina; consumers; porabniki; recesija; recession; Slovenia; Slovenija; stališča; values; vrednote